Isolation of alkaliphilic bacteria producing highly alkaline thermostable lipase - Mad Zain, Azian Ezeila (2015)
Lipase known as triacyglycerol hydrolases (EC3.1.1.3) is use to catalyze the hydrolysis of triaclyglycerol to glycerol and fatty acid. Naturally found in nature and basically derived from various sources such as bacteria, archaea, animals, plants and fungi. Lipase is industrially important and commercially used in industrial such as detergent, food, leather and bioremediation. The aim of this thesis is to screen and isolate bacteria producing highly alkaline and thermostable lipase from hot springs in Malaysia. The identification was done by biochemical tests and 16S rDNA gene sequencing. Follow by characterization of crude lipase on different temperature and pH. Forty eight isolates were selected during first screening on tributyrin agar plate that showed clear halo zones. All forty eight isolates were tested for gram staining for morphology identification. Total of sixteen isolates were chosen from the gram staining and test for second screening on rhodamine B agar plate for the confirmation as lipase producing bacteria. Then, all sixteen isolates were test for lipase production and five isolates were further choosen based on higher lipase activity. All five isolates were gram positive rod. Biochemical test results revealed that all five isolates (T4, T3, B1,G and 20) belong to genus Bacillus. Identification of 16S rDNA showed all isolates were Bacillus licheniformis with different strain. Lipases from two isolates identified as Bacillus licheniformis G and Bacillus licheniformis 20 were characterized. Lipase isolated from B. licheniformis strain G exhibited an optimum temperature of 65 °C and optimum pH at 8.0. while, B. licheniformis strain 20 produced extracellular lipase with optimum temperature and pH of 50 °C and pH 8.0 respectively.